PENDAMPINGAN PENYUSUNAN APLIKASI SISTEM INFORMASI AKUNTANSI GROUND HANDLING PADA KOPERASI KARYAWAN ANGASA PURA 1 SEMARANG DENGAN MENGGUNAKAN MICROSOFT EXCEL - Adhi, Daniel Kartika; Wahyuningsih, Panca; Harminingtyas, Rudika; Widowati, Maduretno (STIE Pelita Nusantara, 2023)
Community service is an activity that aims to help certain communities in several activities. This activity is one part of the Tri Dharma of Higher Education, a mentoring activity for the preparation of an accounting information system application using Microsoft Excel. This mentoring activity starts from analyzing problems to preparing financial reports for the ground handling unit Kokapura using the Microsoft Excel application. The choice to use the Microsoft Excel application is because this application is already available in Microsoft Office and the use of Microsoft Excel has been widely practiced in the community.The results of this activity are expected to record transactions and prepare financial reports for the ground handling unit in accordance with SAK ETAP, more accurately and the process will be faster. Keywords: Cooperatives, Accounting Information Systems and Financial Statements